Genomic profiling of non-small cell lung cancer with the rare pulmonary lymphangitic carcinomatosis and clinical outcome of the exploratory anlotinib treatment - Dong, Changqing; Cheng, Wanwan; Zhang, Meiling; Li, Si; Zhao, Lele; Chen, Dongsheng; Qin, Yong; Xiao, Mingzhe; Fang, Shencun (Frontiers in Oncology, 2022)
Background: To evaluate a potential treatment for this group of patients, our study aimed to provide a clinical and genomic profile of patients with non-small cell lung cancer (NSCLC) and rare malignant pulmonary lymphangitis carcinomatosis (PLC). Methods: We retrospectively reviewed patients with NSCLC who developed PLC. The genomic alterations, tumor mutation burden (TMB), and microsatellite instability (MSI) based on DNA-based next-generation sequencing were reviewed and compared in a Chinese population with lung adenocarcinomas (Chinese-LUAD cohort). Clinical outcomes after exploratory anlotinib treatment and factors influencing survival are summarized. Results: A total of 564 patients with stage IV NSCLC were reviewed, and 39 patients with PLC were included. Genomic profiling of 17 adenocarcinoma patients with PLC (PLC-LUAD cohort) revealed TP53, EGFR, and LRP1B as the three most frequently altered genes. EGFR was less mutated in PLC-LUAD than Chinese-LUAD cohort of 778 patients (35.3% vs. 60.9%, P = 0.043). BRIP1 was mutated more often in the PLC-LUAD cohort (11.8% vs. 1.8%, P= 0.043). Two patients presented with high tumor mutational burden (TMB-H, 10 mutations/MB). Combing alterations in the patient with squamous cell carcinoma, the most altered pathways of PLC included cell cycle/DNA damage, chromatin modification, the RTK/Ras/MAPK pathway and VEGF signaling changes. Fourteen of the participants received anlotinib treatment. The ORR and DCR were 57.1% and 92.9%, respectively. Patients achieved a median progression-free survival of 4.9 months and a median overall survival of 7 months. The adverse effects were manageable. In patients with adenocarcinoma, the mPFS (5.3 months vs. 2.6 months) and mOS (9.9 months vs. 4.5 months) were prolonged in patients receiving anlotinib treatment compared to those receiving other treatment strategies (P < 0.05). Conclusion: Patients with PLC in NSCLC demonstrated distinct genetic alterations. The results improve our understanding of the plausible genetic underpinnings of tumorigenesis in PLC and potential treatment strategies. Exploratory anlotinib treatment achieved considerable benefits and demonstrated manageable safety.